ANALISIS PRODUKTIVITAS PEKERJAAN PENULANGAN KOLOM 20X30 PADA PROYEK PEMBANGUNAN GUDANG LOGISTIK DI POLRES LAMONGAN - Sharvina, Ainun Nurin; Sugfa, Mochamad Reyza Putra Sugfa Putra; Latif, Muhammad; Rochmania, Auliya; Fajri, Nuriya Yasmina; Husodo, Ibnu Toto (Universitas PGRI Semarang, 2026)
Productivity is a crucial indicator in assessing the efficiency of construction project implementation. This study aims to analyze the productivity of reinforcement work on 20x30 cm columns in the construction project of the Logistics Warehouse at the Lamongan Police Headquarters. The research employed a descriptive quantitative method with a case study approach, using data from field observations, documentation, and interviews. The results indicate that the actual labor productivity for rebar installation was 80.69 kg/OH. This value is compared to the national productivity standard outlined in the Ministry of Public Works and Housing Regulation (Permen PUPR) No. 8 of 2023, which is 90 kg/OH. Thus, the productivity observed on-site is 9.31 kg/OH or approximately 10.34% below the standard. Factors influencing this discrepancy include worker skill, work methods, site conditions, and the availability of tools and materials. The study recommends improvements in worker training, optimization of supporting equipment, and enhanced time management and supervision to increase productivity in similar projects